Biotic Potential and Life Table of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) from Three Brazilian Regions - Silva, I. F. [UNESP]; Baldin, E. L.L. [UNESP]; Specht, A.; Sosa-Gómez, D. R.; Roque-Specht, V. F.; Morando, R. [UNESP]; Paula-Moraes, S. V. (Springer Nature, 2018)
This study aimed to evaluate the biotic potential and life table of individuals of Helicoverpa armigera (Hübner) from different host plants (citrus, corn, and cotton) and Brazilian states (São Paulo, Distrito Federal, and Bahia) in artificial diet, under laboratory conditions (25 ± 1°C, 70 ± 10% RH, 14 h photophase). The longevity, pre-, post- and oviposition periods, fecundity, and fertility of 15 mating pairs per origin were evaluated. We also compared the reproductive parameters of each group of insects (São Paulo (SP), Distrito Federal (DF), and Bahia (BA)), including the net reproductive rate (Ro), mean generation time (T), intrinsic rate of increase (rm), and finite rate of increase (λ). Microsatellite analysis from individuals collected in different locations and host plants did not show differences among the parental insects. It was verified that parental progeny collected in cotton fields from Bahia had a higher biotic potential, a higher reproductive rate (Ro), and a better fecundity compared to the insects from remaining regions. The life table charts indicate that the highest values for the reproductive parameters of the Bahia progeny are associated with higher specific fertility, particularly in early adulthood. The greatest biotic potential of the Bahia progeny may be due to increased selection pressure from the insecticide used (organophosphate and pyrethroid) on cotton crops compared to that of other crops, as well due to the massive adoption of Bt cotton-producing areas of that state from 2013 outbreaks.
Keywords: fecundity; longevity; offspring; Old world bollworm; population dynamics